2002
DOI: 10.1002/1522-2675(200207)85:7<2183::aid-hlca2183>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Influenza Virus Replication in MDCK Cells by Circular Dumbbell RNA/DNA Chimeras with Closed Alkyl Loop Structures

Abstract: Dedicated to Professor Wolfgang Pfleiderer on the occasion of his 75th birthdayWe have demonstrated that a new type of circular dumbbell RNA/DNA chimeric oligonucleotide (CDRDON) with two closed nucleotide or alkyl loop structures (hexa-ethylene glycol) inhibits influenza virus A replication in MDCK cells. The enzymatic synthesis of circular dumbbell RNA/DNA chimeric oligonucleotides was achieved by enzymatically ligating a self-complementary phosphorylated oligonucleotide with T4-RNA ligase. The CDRDON-Al, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…After 2 h incubation, 36% of Db-23 retained its sequence in contrast to 6% of L-23. In this condition, no siRNA-1 was detected after 2 h. This improved stability of Db-23 can be attributed to its endless structure, as also reported for DNA dumbbells. 3e,f,4b Next, Db-23, L-23, and siRNA-1 were incubated in 20% human serum at 37 °C (Figure c). In human serum, the differences in stability were not as clear as those observed with SVPD.…”
supporting
confidence: 71%
“…After 2 h incubation, 36% of Db-23 retained its sequence in contrast to 6% of L-23. In this condition, no siRNA-1 was detected after 2 h. This improved stability of Db-23 can be attributed to its endless structure, as also reported for DNA dumbbells. 3e,f,4b Next, Db-23, L-23, and siRNA-1 were incubated in 20% human serum at 37 °C (Figure c). In human serum, the differences in stability were not as clear as those observed with SVPD.…”
supporting
confidence: 71%
“…3 In addition, Hamazakia et al have presented circular dumbbell RNA/DNA chimeras typical of closed-alkylloop structures to achieve higher nuclease resistance. 4 In this work, we proposed a novel prodrug-type ASON that bears a dumbbell conformation with responsive disulfide switches (referred to here as "dumbbell-shaped ASON," DS-ASON). DNA dumbbell conformation consists of two hairpin domains at both ends of the strand; they have been utilized as typical models to analyze structures and functions in DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al have reported that ASONs featuring an alkyl hairpin-end conformation have improved resistance to degradation by nucleases . In addition, Hamazakia et al have presented circular dumbbell RNA/DNA chimeras typical of closed-alkyl-loop structures to achieve higher nuclease resistance …”
Section: Introductionmentioning
confidence: 99%